Using Peer Correction towards Students Writing Ability In Writing Analytical Exposition Text At Senior High School - Jonggoria Najogi; Aryuliva Adnan (Journal of English Language Teaching, 2019)
AbstractThis paper discusses the use of the Peer Correction Technique in teaching writing on analytical exposition text at Senior High School. This technique is applied to help the students in organizing their ideas. In addition, it allows the students to share and exchange their ideas or information to be corrected by their peers in a pair group discussion. Thus by correcting each others’ work, students can gain their critically and analytically thinking. Students also may gain their confidence and interested since their writing is corrected by their peers. Besides, students can also take part actively. By applying the Peer Correction Technique in writing analytical exposition text, the teacher can reach the goal of teaching analytical exposition text to senior high school students. In other words, this technique can help the teacher in teaching writing analytical exposition text to the students.Keywords: Writing, Analytical Exposition Text, Peer Correction Technique